PEMETAAN PENGGUNAAN ALAT EVALUASI MATA PELAJARAN AKUNTANSI KELAS X AKUNTANSI DI SMK NEGERI 1 SOOKO MOJOKERTO - EKA NUR MUSTAFIDAH (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
This study aims to determine the type of evaluation tool in SMK Negeri 1 Sooko Mojokerto and reasons teachers use this type of tool evaluation, determine the feasibility of evaluation tools and know the attitudes of the students during the evaluation process and the students' response to the use of the evaluation tool. This study is a descriptive research. The results showed that the evaluation tool used was the type of test instrument design descriptions with reasons for students to analyze and apply accounting transactions. Based on the review of the results obtained expert evaluation tool that accounting evaluation tool deserves to be tested, and the results of quantitative analysis of evaluation tools considered valid, reliable, poorly differentiated power, level of difficulty is very easy to Question 1 and Question 2 is easy. Students' response to the accounting evaluation tool is excellent and the attitude of the students showed poise and honest in the evaluation process. Keywords: Evaluation Tool